TEOS Modified With Nano-Calcium Oxalate and PDMS to Protect Concrete Based Cultural Heritage Buildings - Kapetanaki, Kali; Vazgiouraki, Eleftheria; Stefanakis, Dimitris; Fotiou, Afroditi; Anyfantis, George C.; García-Lodeiro, Ines; Blanco-Varela, Maria T.; Arabatzis, Ioannis; Maravelaki, Pagona N. (Frontiers in Materials, 2020)
Cultural Heritage constructions of 20th century consist largely of mortar and concrete substrates. These concrete structures have suffered different types of decay processes. One of the most widely used consolidants is the Tetraethoxysilane (TEOS), which forms the basis of most existing commercial strengthening agents to protect porous building materials against deterioration. A novel, nontoxic strengthening and protective agent for mortar and concrete substrates was synthesized in a one-pot sol-gel procedure, incorporating in TEOS, Polydimethyl siloxane (PDMS) and nanoparticles of synthesized calcium oxalate (CaOx). PDMS provided hydrophobicity and reduced surface tension that causes cracks on the surface of produced xerogel. The synthesized nanocomposite both in sol and xerogel form was assessed with a variety of analytical techniques (FTIR, XRF, SEM, Optical Microscopy, Dynamic Light Scattering, Thermogravimetric analysis). The excellent physical properties of the produced colloidal solution of the nanocomposite, such as low viscosity and density, allow a penetration up to 2 cm from the surface in the treated cement mortars. This involved improvement of the mechanical and physical properties, such as the dynamic modulus of elasticity and increased water repellency. The treated cement mortars exhibited well-preserved aesthetic surface parameters and significant maintenance of the treatment. Furthermore, no harmful byproducts were identified indicating the nanocomposite compatibility to the siliceous and carbonate nature of the treated cement mortars.